Understanding the medical diagnosis of child maltreatment a guide for nonmedical professionals - Brittain, Charmaine. (Oxford University Press, 2005)
"Provides a step-by-step guide to frequently asked questions concerning the medical aspects of child abuse and neglect. Designed for the nonmedical professional, this guide covers burns, fractures, poisoning, sexual abuse, neglect, substance abuse, and working with medical providers. Includes charts, illustrations, checklists, and resources"--Provided by publisher.